Green Criminology: Evolution, Typology, and Legal Framework for Environmental Protection - Muhamad Pelengkahu (Ius Poenale, 2025)
Green criminology (GC) offers a critical lens for understanding the dynamics of environmental harm, moving beyond Classical Criminology (CC Green Criminology (GC) offers a framework for understanding environmental harm, extending beyond Classical Criminology to include the rights of ecosystems, non-human species, and future generations. This article traces the evolution of GC, outlines key environmental crime typologies, and examines its relevance for legal and policy responses in Indonesia. Using a normative juridical approach and secondary data, the study assesses Law No. 32 of 2009 on Environmental Protection and Management and related sectoral statutes in addressing illegal logging, wildlife trafficking, pollution, and land degradation. Findings reveal weak enforcement due to fragmented institutions, inadequate sanctions, corruption, and corporate–political influence, highlighting that these offences represent systemic harm. The study concludes that advancing environmental justice requires legal reform, stronger institutional coordination, public engagement, and international cooperation. GC provides a pathway for embedding ecological justice and sustainability into more effective and equitable environmental governance.